Examining the influence of self-esteem and digital literacy on professional competence factors in dental education: A cross-sectional study - Ceylan, Gülsüm; Eken, Melike Özlem; Yürük, Selen; Emir, Faruk (MDPI, 2023)
This study aims to investigate the effects of digital literacy and self-esteem on dental students' perceptions of professional competence and to provide recommendations for improving educational programs in dental schools. A mixed-methods, descriptive, and relational scanning design was employed, using a questionnaire comprising demographic information, the Rosenberg Self-Esteem Scale (RSES), the Digital Literacy Scale (DLS), and the Professional Competence Scale (PCS). The sample included 427 dental students in Istanbul, Turkey. Statistical analyses included Cronbach Alpha, Confirmatory Factor Analysis, Mann-Whitney U, Kruskal-Wallis, Spearman's rho correlation, and the Generalized Linear Model (Logit Model). The majority of participants were female (65.6%), aged 21 or older (85.2%), and in their 4th grade of study (35.2%). There were no significant differences in PCS scores concerning gender, age, grade, type of residence, and residence location (p > 0.05). However, PCS scores were significantly higher among those who listed dentistry among their top five preferences, expressed high satisfaction with education, and demonstrated high professional interest (p < 0.05). A significant, positive correlation was observed between PCS and RSES (r = 0.398; p < 0.01), DLS (r = 0.404; p < 0.01), preference (r = 0.120; p < 0.05), education satisfaction (r = 0.298; p < 0.01), and occupational interest (r = 0.502; p < 0.05). Furthermore, the Logit Model analysis revealed that RSES (B = 0.290; p < 0.01), DLS (B = 0.258; p < 0.01), education satisfaction (B = 0.806; p < 0.05), and occupational interest (B = 3.825; p < 0.01) significantly influenced PCS. The findings underscore self-esteem and digital literacy's integral role in shaping dental students' perceptions of their professional abilities. Digital literacy is a substantial pillar supporting students' professional competency. Coupled with a genuine interest in the field and bolstered self-confidence, digital literacy proves instrumental in enhancing students' academic success in dentistry. By emphasizing and expanding upon digital literacy content within the curriculum, universities can further propel advancements in the dental domain. As such, it is pivotal for dental institutions to weave strategies into their educational fabric to elevate students' self-esteem and digital proficiency.
Keywords: Dental Education; Dentistry Students; Digital Literacy; Self-Esteem